The effects of synchronous music on 400-m sprint performance - Simpson, S. D.; Karageorghis, C. I. (Journal of Sports Sciences, 2007)
The aim of the present study was to assess the effects of motivating and oudeterous (neither motivating nor demotivating) synchronous music on 400-m sprint performance while controlling for the potential confound of pre-performance mood. A panel of volunteer Caucasian males (n = 20; mean age = 20.5 years, s = 1.2) rated the motivational qualities of 32 musical selections using the Brunel Music Rating Inventory-2. An experimental group of volunteer Caucasian males (n = 36; mean age = 20.4 years, s = 1.4) completed three 400-m time trials under conditions of motivational music, oudeterous music, and a no-music control. Pre-performance mood was assessed using the Brunel University Mood Scale (BRUMS). A series of repeated-measures analyses of variance with Bonferroni adjustment revealed no differences in the BRUMS subscales. A repeated-measures analysis of variance on the 400-m times showed a significant effect (F1.24, 42.19 = 10.54, P < 0.001, ?2 = 0.24) and follow-up pair wise comparisons revealed differences between the synchronous music conditions and the control condition. This finding supported the first research hypothesis, that synchronous music would result in better performance than a no-music control, but not the second hypothesis, that performance in the motivational synchronous music condition would be better than that in the oudeterous condition. It appears that synchronous music can be applied to anaerobic endurance performance among non-elite sportspersons with a considerable positive effect.